Restructuring and Competitiveness of Economy - Valentinavičius, Stasys (Ekonomika, 1997)
The article analyzes the new trends in the structural changes of Lithuanian economy in 1993–1998 and problems of foreign trade. The economic factors which increase the competitiveness of firms in the world market are dealt with as well. The main goals of the Covernment economic policy and factors influencing economic competitiveness of the firms under market economy are also defined.